Ubiquitous L1 Mosaicism in Hippocampal Neurons - Upton, Kyle R.; Gerhardt, Daniel J.; Jesuadian, J. Samuel; Richardson, Sandra R.; Sánchez-Luque, Francisco J.; Bodea, Gabriela O.; Ewing, Adam D.; Salvador-Palomeque, Carmen; van der Knaap, Marjo S.; Brennan, Paul M.; Vanderver, Adeline; Faulkner, Geoffrey J. (Cell, 2015)
Somatic LINE-1 (L1) retrotransposition during neurogenesis is a potential source of genotypic variation among neurons. As a neurogenic niche, the hippocampus supports pronounced L1 activity. However, the basal parameters and biological impact of L1-driven mosaicism remain unclear. Here, we performed single-cell retrotransposon capture sequencing (RC-seq) on individual human hippocampal neurons and glia, as well as cortical neurons. An estimated 13.7 somatic L1 insertions occurred per hippocampal neuron and carried the sequence hallmarks of target-primed reverse transcription. Notably, hippocampal neuron L1 insertions were specifically enriched in transcribed neuronal stem cell enhancers and hippocampus genes, increasing their probability of functional relevance. In addition, bias against intronic L1 insertions sense oriented relative to their host gene was observed, perhaps indicating moderate selection against this configuration in vivo. These experiments demonstrate pervasive L1 mosaicism at genomic loci expressed in hippocampal neurons. [Display omitted] •An estimated 13.7 somatic L1 insertions occur per hippocampal neuron, on average•Target-primed reverse transcription drives somatic L1 retrotransposition•Somatic L1 insertions sense oriented to introns are depleted in neurons and glia•Hippocampus genes and enhancers are strikingly enriched for somatic L1 insertions Somatic genome mosaicism among neurons has the potential to impact brain function. L1 retrotransposons mobilize extensively in hippocampal neurons, preferentially in hippocampally expressed loci, and are depleted from mature neurons when oriented in the most deleterious configuration to host genes, suggesting functional significance.